Subcarrier Allocation and Cooperative Partner Selection Based on Nash Bargaining Game for Physical Layer Security in OFDM Wireless Networks. (24th March 2016) - Huang, Shuanglin; Jing, Aixia; Tan, Jianjun; Xu, Jian; Li, Maozhen
Summary: Most orthogonal frequency division multiplexing (OFDM) cooperative schemes in wireless communication system are poor in secure transmission. Based on the Nash bargaining game (NBG), this paper presents a method of OFDM system cooperative scheme restricted in physical layer security. In the model, each wireless node can act as not only a source node, but also a potential relay node. The sub‐carrier allocation problem among selfish nodes is formulated as a two‐persons bargaining game to guarantee fairness. It is proved that the Nash bargaining solution (NBS) of sub‐carriers allocation is existence of unique Nash equilibrium. Based on the bargaining algorithm and the Hungarian method, a multiple‐users partner selection algorithm is proposed in this paper. Simulation results indicate that the subcarrier allocation fairness is dependent on how much rate increase its partner can make. The proposed partner selection algorithm based on the Hungarian method can improve the overall secrecy rate of the network. Copyright © 2016 John Wiley & Sons, Ltd.